(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The article deals with the issues of anthropogenic spatial-temporal changes in the forest cover of Tavush Region. In particular the case of Ijevan Forest enterprise is presented, the negative consequences of deforestation were identified and studied through the following indicators: changes in the forest area and species composition of the forest, fragmentation of the forest massives and changes in the forest boundary-lines, dynamics of landslides and mud-flows.